Bioelectricity generation by microbial degradation of banana peel waste biomass in a dual-chamber S. cerevisiae-based microbial fuel cell. (January 2023) - Verma, Manisha; Mishra, Vishal
Abstract: Microbial fuel cells (MFCs) are considered as an emerging and cost-effective technology for treating organic waste along with bioelectricity generation. The present study evaluates the performance of S. cerevisiae- based H-shaped microbial fuel cell with banana peel waste as substrate, operated for 30 days in three cycles. Dried banana peel and banana slurry substrates were prepared with initial COD of 1126 ± 41 mg. L −1 and 1366 ± 64 mg. L −1 respectively. Dried banana peel powder was fed into two MFCs, one with no inoculant and the other with S. cerevisiae . Dried banana peel powder without inoculant yielded negligible power output, whereas dried banana peel powder with S. cerevisiae generated a maximum power density of 2.2 ± 0.1 mW m −2 . The banana peel slurry was fed into two different MFCs one was with S. cerevisiae and another was without S. cerevisiae. Banana slurry with S. cerevisiae generated a maximum power output of 86.9 ± 0.4 mW. m −2 . Banana peel slurry without inoculation, generated a maximum power output of 44.6 ± 0.8 mW. m −2 . Microbial community analysis indicated that the high-power output obtained from banana slurry-based MFCs was due to the presence of indigenous microbial consortia. Up to 70–88% COD removal was recorded in MFCs with banana slurry, however, 18–44% of COD removal was observed in MFCs with dried banana peel powder. It was also observed that the simple saccharides available in banana peel waste were consumed by S. cerevisiae and other indigenous microbes in the anode chamber. The microbial community released electrons in the anode chamber, which were responsible for voltage generation in MFC. Graphical abstract: Image 1 Highlights: Banana peel waste characterization. Use of banana peel waste as substrate. Use of Saccharomyces cerevisiae as anode biocatalyst. Stainless steel anode modification by activated carbon. Metagenomic analysis of banana slurry to identify microbial community.